Pengaruh Sistem Administrasi Pendidikan terhadap Peningkatan Kinerja Guru di Sekolah-Sekolah Bengkalis - Suri, Dian Ratna (Lembaga Yasin AlSys, 2024)
A good education administration system is expected to help facilitate teachers' duties in planning, implementing, and evaluating teaching and learning activities. However, in many schools, there are still problems related to the ineffective administrative system, which has an impact on the performance of teachers in carrying out their duties. This study aims to measure the influence of the education administration system on improving teacher performance in schools in Bengkalis. The method used in this study is a quantitative approach with a survey design. This study aims to measure the influence of the education administration system on improving teacher performance in schools in Bengkalis. The results of this study can be concluded that a good education administration system has a significant effect on improving teacher performance in schools in Bengkalis. This is evidenced by the results of regression analysis which shows a regression coefficient of 0.65 (p-value 0.000), which indicates that improvements in the administrative system can improve teacher performance by up to 65%. In addition, the data also shows that schools that implement a digital-based administration system have a higher average teacher performance, which is 82.6%, compared to schools that use a manual system, which only reaches 75.4%. Thus, the improvement of the administrative system, both through technology and managerial improvement, can increase the effectiveness of teachers' work in learning activities. This is evidenced by the finding that schools led by principals who support well-organized administration show an average teacher performance of 84.3%, compared to 71.8% in schools that do not support good administration. The data also shows that teachers who take part in administrative training have an average performance of 80.2%, higher than those who do not take part in training, which only recorded 72.9%.